Biological deodorization filter tank device for sewage - LIU YANGYUAN; LI GUANGSHENG; LEI LIRONG (2021)
The utility model discloses a sewage biological deodorization filter tank device which comprises a sewage collection system, a biological reaction tank, a filter bed and a controller which are connected in sequence, a return pipe is arranged between the biological reaction tank and the filter bed to form circulation return, aeration devices are arranged in the biological reaction tank and the filter bed respectively, and biological fillers are arranged in the biological reaction tank. A biological filter material is arranged in the filter bed, a backflow valve and a water quality detector arearranged at the joint of the filter bed and the backflow pipe, the filter bed is provided with a second air outlet, a gas valve and a gas detector are arranged on the second air outlet, and the secondair outlet is further connected with an aeration device. And the return valve, the gas valve, the gas detector and the water quality detector are electrically connected with the controller respectively. 本实用新型公开一种污水生物除臭滤池装置，包括